INSECTICIDE MARSHAL® EC INDUCES TERATOLOGICAL CHANGES IN THE EMBRYOS OF GALLUS domesticus. - P. MATHUR; N. TAPARIA; K. NITU; L .SHAHANI (International Journal of Pharma and Bio Sciences, 2013)
Present study was designed to investigate the toxic effects of Carbosulfan 25% EC Marshal on the developing chick embryo at critical period of its developmental stage. Fertilized eggs of pure breed of chick (BV 300) were immersed in low, medium and sub lethal concentrations of the toxicant for 60 minutes on day 4 of incubation. The gross morphological and skeletal features were studied on day 10 and day 15 of the incubation period. The pesticide caused musculoskeletal deformities in skin, limbs, head, neck, skull, lower body and overall reduction in ossification of skeleton. The embryolethality percentage was highest at the highest dose and lower in the lowest dose. However, incidence of malformations was found to be significant and showed increase with the increasing concentrations of the toxicant. Thus, insecticide Marshal EC with active ingredient Carbosulfan is a potent teratogen with reference to avian systems.